2016
DOI: 10.1039/c5cc07781h
|View full text |Cite
|
Sign up to set email alerts
|

A sustainable protocol for the facile synthesis of zinc-glutamate MOF: an efficient catalyst for room temperature CO2fixation reactions under wet conditions

Abstract: A water stable zinc-MOF (ZnGlu) catalyst was facilely prepared from the proteinogenic amino acid, l-glutamic acid at room temperature in aqueous medium. CO2 fixations were promoted by the ZnGlu catalyst's inherently coordinated water and externally added water in yielding cyclic carbonate and cyclic urethane at room temperature. This eliminates the need for catalyst activation, making ZnGlu a ready-to-use catalyst. The enhanced CO2 cycloaddition with added water hints at the application of ZnGlu in wet flue ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
82
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(84 citation statements)
references
References 47 publications
1
82
0
1
Order By: Relevance
“…In these functionalized COFs, the turnover number (TON) of COF-HNU3 was as high as 495 000 (Table 1, entry 1), which is probably ar esulto fi ts high surfacea rea. [47,48] The as-prepared COF-HNU3 and COF-HNU4 have al arge amount of imidazolium cations and Br À anions,w hich can form hydrogen bonds with the epoxide, thus promoting the reaction of epoxides with CO 2 . Nevertheless,C OF-HNU2w ithoutc atalytic sites showedavery low catalytic activity under the same reaction conditions (entry 7).…”
Section: Resultsmentioning
confidence: 99%
“…In these functionalized COFs, the turnover number (TON) of COF-HNU3 was as high as 495 000 (Table 1, entry 1), which is probably ar esulto fi ts high surfacea rea. [47,48] The as-prepared COF-HNU3 and COF-HNU4 have al arge amount of imidazolium cations and Br À anions,w hich can form hydrogen bonds with the epoxide, thus promoting the reaction of epoxides with CO 2 . Nevertheless,C OF-HNU2w ithoutc atalytic sites showedavery low catalytic activity under the same reaction conditions (entry 7).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it was observed that the alkyl chain of the quaternary ammonium salts affected the carbonate yield significantly (Entry 2–5). The reactivity decreased following the size of the cations, that is, n Bu 4 N + > n ‐Pr 4 N + >Et 4 N + >Me 4 N + , Table suggesting the reduced interaction of Br − and quaternary ammonium ions favored the activity of this reaction, and thus n Bu 4 NBr with the lowest interaction exhibited the best performance …”
Section: Resultsmentioning
confidence: 99%
“…The reactivity decreased following the size of the cations, that is, nBu 4 N + > n-Pr 4 N + > Et 4 N + > Me 4 N + ,T able 1s uggesting the reduced interaction of Br À and quaternary ammonium ions favoredt he activity of this reaction,a nd thus nBu 4 NBr with the lowest interaction exhibited the best performance. [67] Binary catalytic systems for the reactions of epoxidesw ith CO 2 coupling usually combine aL ewis acid to make the ringopeningp rocedure energetically and an anionic or basic moiety to bind and activate the polar carbon-oxygen bonds of CO 2 molecule for subsequent insertion. On the basis of these considerations and ther esultso fM OF-catalyzed cycloaddition of CO 2 in this study and literature, [55,56,68] ap ossible reaction path for H-ZnCo-ZIF-catalyzedc ycloadditiono fC O 2 with epoxides is proposed in Scheme 1.…”
Section: Catalytic Cycloaddition Of Co 2 With Epoxidementioning
confidence: 99%
“…In this context, 100 %a tom economical cycloaddition of CO 2 with epoxidesi so ne of the most promising and studied reactions [7][8][9] because the generated five-membered cyclic carbonates can be used as polar solvents, important chemical intermediates, and electrolytes in lithiumb atteries. For the cycloadditiono fC O 2 with epoxides, many homogeneous and heterogeneous catalyst systems have been developed, including alkali metal salts, [10] ionic liquids, [11][12][13] quaternary ammonium and phosphoniums alts, [14][15][16] metal oxides, [17] transition-metalc omplexes, [18][19][20][21][22] functional polymers, [23][24][25][26] and metal-organic frameworks (MOF), [27][28][29][30][31] etc. We have also synthesized Gd-based MOF materials for activating epoxides in the cycloaddition with CO 2 .…”
Section: Introductionmentioning
confidence: 99%